Bringing Personas To Life: User Experience Design through Interactive Coupled Open Innovation - Lynn Coorevits; Dimitri Schuurman; Kathy Oelbrandt; Sara Logghe (Persona Studies, 2016)
A frequently used technique to enable user involvement during the course of a software design project is the development of personas. Modeling personas helps developers to establish a stronger user focus and act as a constant reminder for whom one is and is not designing. Within this paper we propose coupled interactive open innovation through iterative user involvement, such as in a Living Lab approach, as a way to improve the effectiveness of personas and scenarios. Interactive coupled open innovation addresses user needs and creates new opportunities by using a trial-error learning process. This increases efficiency, augments stakeholders’ collaboration and facilitates co-creation. By involving real users who mirror the constructed personas in subsequent development steps, traditional persona development is enriched. This iterative process elicits new understandings and meanings of domain specific and market knowledge by positioning the development project in a ‘real-life’ context. The input of each step in the process translates towards and provides the technical team with potential input to develop iterations of the design. In this paper we provide a framework, based on interactive coupled open innovation, for persona development that will allow an optimized user experience by bringing personas and their scenarios to life in the design project.